Gerald Thomas in Émile Benoit’s living room - Hanlon, Helen (1988)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Folklore Field Trip to Black Duck Brook March 12-March 16, 1988: a report with photos ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Folklore Field Trip to Black Duck Brook March 12-March 16, 1988: a report with photos".